Hypervitaminosis D and Metastatic Calcification in a Colony of Inbred Strain 13 Guinea Pigs, Cavia porcellus. (July 2015) - Holcombe, H.; Parry, N. M.; Rick, M.; Brown, D. E.; Albers, T. M.; Refsal, K. R.; Morris, J.; Kelly, R.; Marko, S. T.
A commercial diet fed to a colony of inbred strain 13 guinea pigs for approximately 6 weeks was subsequently recalled for excessive levels of vitamin D. Twenty-one of 62 animals exhibited clinical signs, including anorexia, lethargy, and poor body condition. Nine affected and 4 clinically normal animals were euthanized for further evaluation, including serum chemistry, urinalysis, and gross and/or histopathology. Macroscopic findings included white discoloration in multiple organs in 8 animals, and microscopic evaluation confirmed multiorgan mineralization in tissues from 7 animals. Serum 25-hydroxyvitamin D levels were elevated in 10 animals. Serum inorganic phosphorus and alkaline phosphatase levels were increased in all exposed animals; however, total calcium and ionized calcium levels were not significantly higher in exposed animals than in control strain 13 guinea pigs from a different institution. The data support a diagnosis of hypervitaminosis D with metastatic calcification. Following the diet recall, the remaining guinea pigs increased their food intake and regained body condition. Diagnostic testing of 8 animals euthanized approximately 3 months after returning to a normal diet demonstrated that serum parathyroid hormone remained significantly lower, and ionized calcium and ionized magnesium were significantly higher, in recovered animals compared to controls and exposed animals. These results indicate that diagnostic tests other than serum calcium are necessary for a diagnosis of hypervitaminosis D in guinea pigs.